#TITLE_ALTERNATIVE# - ASTRI HAPSARI (NIM: 20508005), RIZQIYA
The nucleus harbors most of the cells genetic material and surrounded by the nuclear envelope consisting of an outer and inner membrane. Thousands of different molecules are transported selectively in and out the nucleus. This transport is regulated by Nuclear Pore Complexes (NPCs) that are embedded in the nuclear envelope. The transport mechanism through NPCs for soluble proteins is well studied and generally the import mechanism requires a Nuclear Localization Signal (NLS), a molecular address, encoded in the amino acid sequence. For some membrane proteins, trafficking through NPCs also requires a NLS sequence but the transport mechanism remains poorly understood. The main reason of these studies is that dysfunction of inner nuclear membrane proteins is linked to several genetic diseases. Understanding how these proteins are transported to inner membrane may be an important aspect in understanding the mechanism of these diseases. Recent experiments showed that although the presence of the NLS sequence is necessary it is not sufficient for membrane protein import through NPCs. The structure around the NLS is also important. Thus, the aim of this experiment is to characterize the structure of NLS-containing domain of yeast inner nuclear membrane protein, Heh2. The gene was cloned into the pBAD vector containing poly-His10 and expressed in Escheriachia coli MC1061. Immobilization Metal Affinity Chromatography (IMAC) and Size Exclusion Chromatography (SEC) were used for purification of the protein domain. Unfortunately, the domain exhibited a non-ideal behavior during purification. We observed that mass calibration with SDS-Page predicts a larger molecular weight than expected (17 kDa extra). In addition, the proteins formed oligomers or aggregates in gel filtration but not in native electrophoresis. Altogether the data indicate that the protein domain has a tendency to oligomerize or aggregate, possibly due to poor folding. However a GFP-fusion of the proteins expressed in the yeast behaved well. The domain has a larger molecular weight (12 kDa extra) than expected, but western and mass spectrometry analysis of the purified protein indicate that this may be caused by a post translational modification, likely sumoylation. Using fluorescent microscopy of live yeast cell we measured extremely high accumulation of the GFP-NLSD fusion in the nucleus, about 10-20-fold higher than in other NLS-GFP constructs. For future structural studies, the GFP-NLSD fusion may well be a better target as it seems to be more stable. The unexpectedly high accumulation of the GFP-NLSD compared to other GFP-NLS fusion will be of great value in biochemical assays, such as transport measurements in isolated nuclei.